Advanced endoscopic imaging techniques in Crohn's disease. (1st April 2014) - Tontini, Gian Eugenio; Vecchi, Maurizio; Neurath, Markus F.; Neumann, Helmut
Abstract: Background: Endoscopy is of pivotal importance in Crohn's disease (CD) patients for diagnosis, surveillance and assessment of disease activity and extent. Device-assisted enteroscopy (DAE) and small-bowel capsule endoscopy (SBCE) have recently changed our endoscopic approach to small-bowel imaging. Furthermore, new advanced endoscopic imaging techniques have been implemented into clinical practice to improve both characterization of mucosal inflammation and detection of dysplastic lesions. Aim: To provide readers with a review about the concept of advanced endoscopic imaging for the diagnosis and characterization of CD. Methods: A literature search on the use of advanced endoscopy techniques in IBD patients was performed. Results: DAE and SBCE allow for deep enteroscopy with high diagnostic yields and low complication's rate but their collocation in the diagnostic algorithm is still not clearly defined. Dye-based chromoendoscopy (DBC) and magnification chromoendoscopy improved dysplasia's detection in long standing colitis and prediction of inflammatory activity and extent. Dye-less chromoendoscopy (DLC) might offer the potential to replace conventional DBC for surveillance. However, both narrow band imaging and i-scan have already shown to significantly improve activity and extent assessment in comparison to white-light endoscopy. Confocal laser endomicroscopy (CLE) can detect more dysplastic lesions in surveillance colonoscopy and predict neoplastic and inflammatory changes with high accuracy compared to histology. Moreover, CLE-based molecular imaging may anticipate the therapeutic responses to biological therapy. Endocytoscopy can identify in vivo inflammatory mucosal cells harboring a new method to assess the mucosal activity. Conclusions: Recent progresses in small-bowel enteroscopy offer several potential benefits to improve both diagnosis and characterization of CD. New advanced endoscopic imaging techniques can improve detection of dysplasia and refine mucosal healing assessment, even looking beyond the morphological parameters revealed by conventional endoscopic imaging.